Estudio Comparativo de Metodologías de Desarrollo de Software para aplicaciones móviles. - Camacho Herrera, Andy Aron (2022)
The Covid-19 pandemic has affected many markets worldwide and the software industry is no exception, so several companies have sought new ways of working to maintain their business. This crisis has brought with it several opportunities, but also many challenges for software developers and suppliers in Latin America. As an opportunity, the demand for software grew, especially in mobile applications, due to several companies in various markets started to offer their services through this type of applications. The challenge that developers had to face was to try to meet this demand in a short time, so they needed to choose a development methodology that would fit these measures. The objective of this Degree Project is to carry out a comparative study of software development methodologies to determine which methodology or stages of these methodologies is best suited for the development of mobile applications. With this purpose the research question is the following: Which software development methodology can be implemented in the creation of mobile applications in times of covid-19 pandemic? Under this context, a correct choice of a software development methodology will allow the creation of mobile applications adapting to turbulent environments. The research question was answered through the execution of three phases, in the first phase, a Systematic Literature Review (SLR) was performed to help determine the most used software development methodologies for mobile applications during the pandemic, resulting in the Prototyping methodology. In this same phase, a comparative matrix was constructed with 34 evaluation criteria divided into four categories; this with the help of a comparative guide of software development methodologies and the SLR. In the second phase, an experimentation environment was developed in an academic environment with the help of a group of students belonging to ninth cycle of the Systems Engineering career of the Universidad Nacional de Loja, which allowed the evaluation of the selected methodology in a real environment through the development of a test mobile application. In the third phase, the evaluation was carried out, where the hypothesis related to the research question was tested and it was determined that Prototyping is a software development methodology that was adapted to the development of the mobile test application with a degree of satisfaction of 91%. It was also possible to determine strengths and weaknesses of Prototyping from the whole research process of this TT. Finally, future work is presented where it is proposed to conduct further research and developing a comparative study of software development methodologies in a business environment, in order to obtain more solid results when choosing a development methodology for mobile applications. Keywords: mobile app, analysis, documentation, evaluation, development methodology, software, Prototyping.